Relationships of the Cyprideis torosa (Ostracoda, Crustacea) with Seasonal Occurrences, Carapace Type and Physicochemical Variables in Kocaçay Delta (Türkiye) - Külköylüoğlu, Okan; Yavuzatmaca, Mehmet; Akay, Enis; Dalkıran, Nurhayat (Eğirdir Su Ürünleri Araştırma Enstitü Müdürlüğü, 2023)
To understand the spatial and temporal continuing occurrence patterns and relationships of Cyprideis torosa to several physicochemical variables, monthly samples from seven stations were collected from Kocaçay Delta (Bursa, Türkiye) between 2018 and 2019. Four (Cyprideis torosa, Koencypris ornata, Candona cf. lindneri, Candona meerfeldiana) of 14 ostracod taxa are new records for the ostracod fauna of Bursa province, where the total numbers of recent species increased to 33. Cyprideis torosa was the only dominant species found in almost all samples throughout the sampling. Based on the carapace type of the species, three groups can be divided as i) Type-1 (smooth carapaces), ii) Type-2 (noded carapaces), and iii) Type-3 (carapaces noded on one valve and smooth/rare on the other). Different occurrence patterns of the species with overlapping ecological ranges were observed among the stations. Except for station 1, all the types were encountered from other stations. Beginning from December 2018, nearly all populations had mostly Type-1 individuals until March. During April-May, individuals with Types-2 and 3 appeared to increase until October, while individuals in the Type-2 group were solely found from three stations (2, 3, and 5) in March and May 2018. There was a significant difference in salinity, magnesium, and calcium values among the stations (P<0.05) but only total nitrogen, temperature, and calcium showed a medium correlation to carapace type. In all cases, populations with noded individuals were found in narrower ecological ranges for those variables than other populations with smooth individuals.
Keywords: Limnology; Limnoloji